Monitoring Akusisi Data Manajemen Energi Listrik, Suhu dan Kelembaban Laboratorium Berbasis Internet of Things (IoT) - Ramona Dyah Safitri; Junaidi Akbar (Universitas Islam Raden Rahmat, Malang, 2024)
In the use of electric energy and the comfort of a person's work in the laboratory, standard limits are required, therefore data management such as voltage, current, power, energy, frequency, power factor in terms of electricity usage, temperature and humidity in terms of comfort is needed to improve a person's work or study, so routine measurements are carried out by manual audits. With the Internet of Things (IoT) technology, it can make it easier to monitor a device from afar. The results of the comparison of sensors and measuring instruments on voltage obtained an error value of 0.0871% and efficiency of 99.91%, current obtained an error value of 4.76% and 95.24% efficiency, power obtained an error value of 7.59% and 92.38% efficiency, energy obtained an error value of 4.813% and 95.17% efficiency, frequency obtained an error value of 0.02% and 99.98% efficiency, power factor obtained an error value of 3.03% and 96.96% efficiency, temperature obtained an error value of 0.73% and 99.26% efficiency, humidity obtained an error value of 5.45% and 95.54% efficiency.